ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN (Studi Pada Bank Umum yang Listed di Bursa Efek Indonesia Tahun 2007-2010) - Arimi, Millatina; Kholiq Mahfud, Mohammad (Faculty of Economics and Business Diponegoro University, 2012)
Bank is one of the financial institution which have activities to raise funds from public in the form of savings and distribute them to the public in from of credit or other form. The purpose of the banking business is gain profit. Ability of the banks in gain profit is measured by return on assets (ROA). The purpose of this research is to examine influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), and BOPO through Return On Asset (ROA) of public banking listed at Indonesian Stok Exchange during 2007-2010. Research using purposive sampling method for taking samples. Data obtained on the basis of publication Annual Bank, obtained 20 samples of General Bank. Samples used in this research are public banking listed at Indonesian Stock Exchange on period 2007-2010. Analysis technique used is multiple linear regression analysis. The results of this research found that Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) hasn’t significant positive effect to Return On Asset (ROA), Non Performing Loan (NPL) hasn’t significant negative effect to Return Asset (ROA), Net Interest Margin (NIM) has significant positive effect to Return On Asset (ROA), and BOPO has significant negative effect to Return On Asset (ROA).